Associations Between the KIAA0319 Dyslexia Susceptibility Gene Variants, Antenatal Maternal Stress, and Reading Ability in a Longitudinal Birth Cohort. (28th July 2016) - D'Souza, Stephanie; Backhouse‐Smith, Amelia; Thompson, John M. D.; Slykerman, Rebecca; Marlow, Gareth; Wall, Clare; Murphy, Rinki; Ferguson, Lynnette R.; Mitchell, Edwin A.; Waldie, Karen E.
Abstract : Maternal stress during pregnancy has been associated with detrimental cognitive developmental outcomes in offspring. This study investigated whether antenatal maternal perceived stress and variants of the rs12193738 and rs2179515 polymorphisms on the KIAA0319 gene interact to affect reading ability and full‐scale IQ (FSIQ) in members of the longitudinal Auckland Birthweight Collaborative study. Antenatal maternal stress was measured at birth, and reading ability was assessed at ages 7 and 16. Reading data were available for 500 participants at age 7 and 479 participants at age 16. FSIQ was measured at ages 7 and 11. At age 11, DNA samples were collected. Analyses of covariance revealed that individuals with the TT genotype of the rs12193738 polymorphism exposed to high maternal stress during pregnancy possessed significantly poorer reading ability (as measured by Woodcock‐Johnson Word Identification standard scores) during adolescence compared with TT carriers exposed to low maternal stress. TT carriers of the rs12193738 SNP also obtained lower IQ scores at age 7 than C allele carriers. These findings suggest that the KIAA0319 gene is associated with both reading ability and general cognition, but in different ways. The effect on IQ appears to occur earlier in development and is transient, whereas the effect of reading ability occurs later and is moderated by antenatal maternal stress. Copyright © 2016 John Wiley & Sons, Ltd.